The response of the retinal vessels to the vitamin D supplementation treatment running title: The retinal vessels and vitamin D supplementation treatment - Sinem Karabulut; Tugba Dübektaş Canbek; Müjdat Karabulut; Okan Akmaz; Aylin Karalezli (Photodiagnosis and Photodynamic Therapy)
Background: We planned to prospectively investigate the response of retinal microvasculature to vitamin D supplementation treatment. Methods: This study was designed as a prospective, longitudinal study. We enrolled healthy adults with vitamin D deficiency. Baseline optical coherence tomography angiography parameters compared after vitamin D supplementation treatment. Results: In the treated group, the mean whole, parafoveal, and perifoveal vessel density in deep capillary plexus were significantly reduced compared to the baseline (p = 0.019, p = 0.023, p = 0.012, respectively). Additionally, the final whole, parafoveal, and perifoveal vessel density in deep capillary plexus were inversely related to the vitamin D changes (Spearman's rho:-0.516, p = 0.024; Spearman's rho:-0.524, p = 0.019; Spearman's rho:-0.569, p = 0.012, respectively). Vascular parameters did not change in the untreated group compared to the baseline. Conclusion: Although the effects of some confounding factors, such as exposure time to sunlight and dietary vitamin D intake in the study, were not yet known, vitamin D supplementation therapy appeared to affect retinal microvasculature. Optic coherence tomography angiography might indicate noninvasively the effectiveness or sufficiency of vitamin D treatment at the microvascular level, although the observed changes in the retinal vessels are as yet not fully understood.